Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1021/la030385+
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Aspects of the Liposome−Wool Interaction in Wool Dyeing

Abstract: Despite the promising application of liposomes in wool dyeing, little is known about the mechanism of liposome interactions with the wool fiber and dyestuffs. The kinetics of wool dyeing by two dyes, Acid Green 27 (hydrophobic) and Acid Green 25 (hydrophilic), were compared in three experimental protocols: (1) without liposomes, (2) in the presence of phosphatidylcholine (PC) liposomes, and (3) with wool previously treated with PC liposomes. Physicochemical interactions of liposomes with wool fibers were studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 15 publications
0
19
0
5
Order By: Relevance
“…The higher removal rate of AT could be attributed to its phospholipidic composition, since lipid degradation is favoured with thermophilic bacteria [8]. As both temperatures used in the present study are higher than the transition temperature of liposome lipids (below 0 • C), the continuous fluid state of these lipids maintains the vesicles without structural alterations [4]. However, high temperatures should cause an increase in fluidity, by decrease of molecular order (viscosity decrease).…”
Section: Batch Kinetic Studies In Mesophilic and Thermophilic Conditionsmentioning
confidence: 77%
See 1 more Smart Citation
“…The higher removal rate of AT could be attributed to its phospholipidic composition, since lipid degradation is favoured with thermophilic bacteria [8]. As both temperatures used in the present study are higher than the transition temperature of liposome lipids (below 0 • C), the continuous fluid state of these lipids maintains the vesicles without structural alterations [4]. However, high temperatures should cause an increase in fluidity, by decrease of molecular order (viscosity decrease).…”
Section: Batch Kinetic Studies In Mesophilic and Thermophilic Conditionsmentioning
confidence: 77%
“…Liposomes are vesicular structures with an internal aqueous phase entrapped by a lipid bilayer. They are formed by surface active biological lipids which are the main constituents of cell membranes [4].…”
Section: Introductionmentioning
confidence: 99%
“…Dyes are synthetic aromatic compounds which can bring bright and firm color to other materials. It is reported that over 100,000 commercially available dyes exist and more than 7x10 5 metric tons of dyes are produced worldwide annually [2]. When a textile fiber is immersed in a solution of dye under suitable conditions, the fiber becomes colored, the color of the solution decreases and dyeing has occurred [3].…”
Section: Introductionmentioning
confidence: 99%
“…Structurally, a wool fiber is an assembly of cuticle and cortical cells held together by the "cell membrane complex" (See Figure 1). The dyeing and diffusion properties of fibers are known as governed by this membranous structure, which is formed predominantly by internal wool lipids [5]. Cross-section diagram of a merino wool fiber [6] Wool cuticle cells (overlapping cells that surround the cortex) are subdivided into two main layers, namely the exocuticle and endocuticle [7].…”
Section: Introductionmentioning
confidence: 99%
“…Reference literature also supports this theory as traditional methods for dyeing wool use elevated temperatures and products that can damage the fibres and that the dyeing and diffusion properties of the wool and fibres are governed by wool lipids, and thus an understanding of how the dyeing process changes these structures is key to its optimisation. 28 Wool dyed with woad and artificially aged (800 h) has been investigated to determine the level of photodegradation. The resulting micro-Raman spectrum (Fig.…”
mentioning
confidence: 99%